Characterization of the Cell Wall Localization of Pneumolysin in Streptococcus pneumoniae. - Price, Katherine. (2017)
Abstract: The bacterium Streptococcus pneumoniaeis a major causative agent of otitis media, pneumonia, bacteremia and meningitis. Pneumolysin (Ply), a member of the cholesterol-dependent cytolytic (CDC) pore-forming toxins, is produced by virtually all clinical isolates of S. pneumoniae, and strains deleted for the pneumolysin gene are severely attenuated in mouse models of colonization and infection. In contrast to all other known members of the CDC family, Ply lacks a signal peptide for export outside the cell. Instead, Ply has been hypothesized to be released upon autolysis, or alternatively, via a non-autolytic mechanism that remains undefined. I show, using cell fractionation and Western blotting, that exported Ply is localized primarily to the cell wall compartment in the absence of detectable cell lysis. Hemolytic assays revealed that this cell wall-localized Ply is active. Cell wall-localized Ply is accessible to extracellular protease and is detergent releasable. Ply released by autolysis cannot re-associate with intact cells, suggesting that there is indeed a Ply export mechanism that is coupled to cell wall localization of the protein. Through truncation and domain swapping analyses, I show that export is dependent on domain 2 of Ply. Additionally, a signal sequence is not sufficient for Sec-dependent Ply secretion in S. pneumoniae, but is sufficient in a surrogate host Bacillus subtilis. Finally, using the native ply sequence, I show that a signal sequence-less protein export pathway is conserved in B. subtilis.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Andrew Camilli.; Committee: Joan Mecsas, Michael Malamy, and Katya Heldwein.; Keyword: Microbiology.